Evaluación de la presencia de ácaros productores de la sarna en perros con dermatitis clínica en la zona urbana del Cantón Echeandía - Villares Dorado, Pedro Alexander (2024)
In this research, a study was conducted to evaluate whether there is the presence of scabies mites in skin lesions or clinical dermatitis in canines in the Echeandía Cantón, Bolívar Province, considering the great importance it has for the health of canines, helping to know if there is a predominant mite in the area. In order to obtain these results, the skin scraping technique was used, which consists of scraping the skin with the help of a scalpel, until achieving a slight redness without bleeding and obtaining the suffering material to place it on a slide, and then take it to be analyzed under a microscope. Using the technique, 80 samples were taken from dogs, of which only one (1%) was positive for Demodex canis, while 99% of the samples were negative. No positive cases of Sarcoptes scabiei were found in any of the samples. The analysis was considering factors such as race, sex and age. As for breed, 13 different breeds were evaluated, the most common being crossbreeds, French Poodles and Golden Retrievers, but all tested negative for Sarcoptes scabiei. Regarding sex, 49 males and 31 females were analyzed, with no significant differences in the presence of the mite among them. Finally, when grouping the dogs into age ranges, no prevalence of Sarcoptes scabiei was detected in any group. The results obtained from the information will be of great importance to support the improvement of animal health and the efficiency in diagnosing the disease, and will also help us to have more research that allows us to have records of the incidence of these mites in the urban area studied.